ალიმენტზე გადაწყვეტილების აღსრულების თავისებურებანი - გაიპარაშვილი, მარიამ / Gaiparashvili, Mariam (My University, 2021)
The document includes the regulations considered most effective in regulating the cases of alimony. Including, the issue of determining the amount of alimony and the enforcement of the decision. Those issues are regulated individually by the member states of the European Union. However, there is a general unified regulation regarding the enforcement of judgments between persons residing in different countries. The study also analyzes the legislation of the United Kingdom, Canada, and the United States of America.
Execution of the decision on alimony
https://web-api.parliament.ge/storage/files/shares/kvleviti-centri/kvlevebi/2/alimenti.pdf